Role of physical agents in vocal rehabilitation: a literature review - Fuentes Aracena, Christopher (Revista de Investigación en Logopedia, 2020)
Physical agents are natural or artificial elements that are applied for the treatment of certain symptoms or pathologies. In vocal rehabilitation, the study of physical agents is an emerging area, where systematic reviews and meta-analyzes are scarce. This, many times, hampers the decision making and the correct choice by the clinician. The objective of this study was to analyze the role of physical agents in vocal rehabilitation. A literature review was conducted through the search for papers in the databases PubMed, EBSCOHost and Scielo. Eligibility criteria were established according to type, year and characteristics of the studies. Six hundred and three (603) papers were assessed, of which, following the analysis of their titles, abstracts and compliance with the eligibility criteria, 16 were selected. Results were delivered based on the number of participants, level of evidence, type and setup of the physical agent, evaluation procedures and instruments and benefits obtained. The most frequently used physical agents in the vocal clinic are electrotherapy (TENS and NMES) and laser therapy. In general, they act as adjuvants in vocal therapy. TENS reduces pain, laryngeal tension and tight voice perception during phonation. NMES benefits the neuromuscular activation of vocal cords, and the laser use allows for the recovery of laryngeal tissues after vocal overloading tasks.
Keywords: physical agents; lasertherapy; TENS; NMES; vocal therapy; dysphonia